“You're Building Trust, You're Building Rapport”: Contributions from Implementers of Health-Focused Community Engagement - Autumn Tamlyn; Sarah Barnes; Yewon Na; Hope White; Matthew Spence; Benjamin Linas; Mari-Lynn Drainoni (Journal of Community Engagement and Scholarship)
Health-focused community engagement (CE) is a common intervention to combat existing healthcare inequity and its disproportionate impact on the health of underserved Black, Indigenous, and People of Color (BIPOC) communities. While health-focused CE may contribute to better health outcomes by establishing feelings of empowerment within the community, strengthening relationships, and increasing a community’s resiliency, the perspective of the implementers is often not considered. The current study aims to address this gap by understanding the experiences, beliefs, values, and assessments of health-focused CE staff.